Welfare models and demand-led growth regimes before and after the financial and economic crisis - Eckhard Hein; Walter Paternesi Meloni; Pasquale Tridico (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2019)
Recently, several interesting attempts have been made at connecting comparative political economy (CPE) approaches, as the Varieties of Capitalism (VoC) theory, with post-Keynesian (PK) research on different demand-led growth regimes in modern capitalism, and for the period of finance-dominated capitalism since the early 1980s in particular. However, we find several problems in the way Kaleckian and PK approaches are interpreted and integrated in modern CPE approaches. Therefore, we first clarify several ambiguities and misunderstandings of PK demand-led growth regimes and their empirical indicators in the recent CPE literature, and, following the recent PK literature, we provide a theoretically consistent and empirically applicable classification of demand and growth regimes under the conditions of finance-dominate capitalism. Second, instead of using the traditional VoC dual classification, we link and confront the PK demand and growth regimes with the recent evolution of Esping-Andersen's (1990) taxonomy which considers five welfare models. Third, we examine the relationships between demand-led growth regimes and welfare models, both before and after the 2007-9 global crisis. For this purpose, we share the qualitative taxonomy suggested by Hay and Wincott (2012), and additionally we quantitatively assess the degree of welfare of each country and its evolution by means of a "principal component analysis" (PCA), which allows us to synthesize four socio-economic indicators in a multidimensional measure of welfare.
Keywords: E02; P16; P51; 330; Demand-led growth; welfare models; comparative political economy; post-Keynesian economics; Varieties of Capitalism